Maximal oxygen uptake is associated with resting endiastolic volume in prepubertal crosscountry skiers - Hallén, J.; Landgraff, H. W.; Sarvari, S. I.; Aaeng, A.; Ansari, H.; Edvardsen, T. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: In adults, a high aerobic power (VO2max) is associated with a high maximal cardiac output. A high cardiac output is achieved by a high stroke volume (SV) which again is achieved by a large left ventricle (LV) end-diastolic volume (EDV) during exercise. If EDV at rest also is associated with VO2max is not known. Furthermore, if these relationships are true also in children is unknown. This study aimed to investigate if there is an association between resting LV EDV and VO2max in a group of prepubertal Norwegian crosscountry skiers. Methods: Seventy-four Norwegian children (boys n=46, age 11.9 ± 0.3 and girls n=28, age 11.9 ± 0.2) were recruited from cross-country ski clubs. VO2max was determined by incremental treadmill running to exhaustion. End-diastolic volume (EDV) and endsystolic volume (ESV) at rest were assessed by 2D echocardiography. Hemoglobin mass (Hbmass) was measured by the optimized COrebreathing method. Results: Heights were 151 ± 7 and 154 ± 7 cm and weights were 39.2 ± 4.91 and 41.0 ± 6.0 kg for boys and girls, respectively, with no significant differences between genders. There was a significant correlation between absolute VO2max (L/min) and LV EDV (ml) (r=0.66; 90%CI 0.53 - 0.76). Relative to body mass the correlation between VO2max (ml/kg/min) and resting EDV (ml/kg) was also significant (r= 0.53; 0.37 - 0.66). Furthermore, ESV correlated positively to VO2max both in absolute values (r=0.47; 0.30 - 0.61) and relative to body mass (r=0.37; 0.19 - 0.53). Resting SV (EDV-ESV) correlated with Hbmass, both in absolute values (r=0.72; 0.61 - 0.80) and relative to body mass (r=0.40; 0.22 - 0.55). There was no correlation between resting ejection fraction and VO2max. Discussion: The association between resting LV EDV, Hbmass and VO2max in absolute values is partly determined by body mass. However, the relatively high correlation coefficients indicate a relatively high reliability of the measurements. VO2max is associated with a high maximal cardiac SV which again is achieved by a large EDV during exercise. The significant correlation found between resting EDV and VO2max normalized for body mass, indicates that maximal EDV during exercise is associated with resting EDV. Furthermore, the positive association between resting ESV and VO2max indicates that those with higher VO2max have a higher cardiac reserve at rest.